Improving the Emotional Distress and the Experience of Hospitalization in Children and Adolescent Patients Through Animal Assisted Interventions: A Systematic Review - Correale, Cinzia; Borgi, Marta; Collacchi, Barbara; Falamesca, Chiara; Gentile, Simonetta; Vigevano, Federico; Cappelletti, Simona; Cirulli, Francesca (Frontiers in Psychology, 2022)
Introduction. Animal Assisted Interventions (AAIs) are increasingly introduced in pediatric care settings as a means to promote the physical, mental, and emotional well-being of hospitalized children and adolescents. Objectives. The aim of this work was to review published studies implementing AAIs in hospital settings and to assess their effectiveness in reducing stress and pain, ameliorating social behavior, quality of life, and mood in pediatric patients. Reviewed interventions were also evaluated for their effects on caregivers’ stress and burden, as well as on the perception of the work environment in hospital staff. Methods. Studies were systematically searched using PubMed, Scopus, ProQuest and Web of Science databases in accordance with PRISMA guidelines. The aim was to identify studies examining the effects of AAIs on behavioral and physiological responses to stress in children and adolescents (0-18 years) formally admitted to a hospital for a stay, as well as in those undergoing a visit for treatments or medical examinations. Results. Of the 350 studies screened, 21 were eligible for inclusion. Most of them focused on stress, pain, and anxiety reduction in pediatric patients, and used both physiological parameters and behavioral observations/scales. All studies employed dogs. Results show the potential of AAIs to reduce anxiety and behavioral distress in pediatric patients while acting on physiological measures associated with arousal. Conclusions. Although further studies of better quality are still needed, the findings of this review may have implications for clinical practices suggesting appropriate planning of AAIs by pediatric healthcare professionals.